Avaliação químico-estrutural e biofarmacêutica de novas formas sólidas multicomponentes de fármacos anti-hipertensivos e antidiabéticos - Luan Farinelli Diniz (2022)
The chemical and structural attributes of active pharmaceutical ingredients (APIs) are directly related to their biopharmaceutical properties. Among these properties, solubility, intrinsic dissolution, and permeability are considered important characteristics of a drug since they modulate bioavailability. In this context, crystal engineering has established itself as one of the most effective tools to improve the biopharmaceutical properties of APIs. In this work, eleven new multicomponent crystal forms, including salts and cocrystals, from the drugs carvedilol (CVD), furosemide (FSM), diltiazem (DIL) and metformin (MET), were rationally designed and had their crystal structures elucidated. Also, the crystalline modifications obtained were fully characterized by diffractometric, spectroscopic, and thermal techniques. Additionally, solubility, intrinsic dissolution, and in vitro permeability studies were also carried out. The two new racemic salts CVD-HCl-H2O and CVD-HBr-H2O crystallized as solid solutions of enantiomers while the CVD-OXA salt crystallized as a racemate. In the solid solutions, the notable miscibility between homochiral units of R‧‧‧R and S‧‧‧S enantiomeric pairs resulted in the formation of this rare system. Regarding solubility, the three new CVD salts promoted considerable improvements in CVD solubility. The design of the FSM solid forms had the main purpose to enhance the low solubility and permeability of the API. These objectives were successfully achieved since the FSM imidazolium salt (FSM-IMI) and the FSM 5-fluorocytosine monohydrate cocrystal (FSM-5FC-H2O) proved to be more soluble and permeable compared to pure FSM. Whit respect to the DIL the two hydrated salts (DIL-OXA-H2O and DIL-SUC-H2O) and the anhydrous salt-cocrystal (DIL-FUM-H2FUM) obtained provided a noticeable reduction in both solubility and intrinsic dissolution rate of the API. This is due to the formation of more efficiently packed crystalline structures. Such evidence was confirmed by estimating the salts energy framework as well as through detailed crystallographic analysis. Finally, the reactions involving MET free base made it possible to obtain the following salts: MET maleate (MET-MAL), malonate (MET-MLN), and saccharinate (MET-SAC). These new three salts were less soluble and dissolved more slowly compared to the commercial form MET-HCl, being all considered potentially promising to compose future controlled-release formulations. Therefore, the results presented in this thesis bring relevant and innovative scientific contributions, especially regarding the possibility of enhancing the biopharmaceutical properties of all APIs involved in this work.